Mathematical activities in school-age educare - Maria Hjalmarsson; Maria Fahlgren; Karin Våge (Social Sciences and Humanities Open, 2025)
Since 2016, the Swedish school-age educare has had a clarified mission regarding knowledge and teaching, and mathematics has been an explicit part of the education. Drawing on six universal mathematical activities, this study aims to contribute knowledge about the experiences and lessons learned within a project in which school-age educare teachers, in collaboration with researchers, plan, implement, and evaluate mathematical activities. The research process was guided by an action learning model and involved four teachers working at one school and represented four departments. The results indicate that the challenges arising during the processes were threefold: (i) gaining a sufficiently clear understanding of the teachers' knowledge and experience with mathematical activities to provide optimal support during the planning phase, (ii) striking a balance between the teachers’ own ideas and the level of guidance provided by the researchers in designing a teaching session, and (iii) planning, conducting, and evaluating instruction within an educational context that is defined only by central content, without specific learning objectives for students. Nonetheless, the study demonstrates the potential of school-age educare to offer students subject-based teaching through practical-aesthetic forms of expression and a play-based pedagogical approach, as well as the opportunity to learn and develop in an educational context where their performance is not formally assessed.